The Effect of Exclusive Breastfeeding on Infant Growth - Eni Adeko; Nila Widya Keswara (Journal of Educational Innovation and Public Health, 2025)
Exclusive breastfeeding for the first six months of life is an important nutritional intervention that plays a role in supporting infant growth and preventing growth disorders. Although the coverage of exclusive breastfeeding in Indonesia has increased, differences in infant growth outcomes based on nutritional sources remain an issue that needs to be examined contextually. This study aims to analyze the effect of exclusive breastfeeding on infant growth at the Labuha Community Health Center, South Halmahera Regency. The study uses a quantitative approach with an observational analytical design and a comparative cross-sectional design. The study sample consisted of 30 infants aged 3–9 months selected using total sampling technique. The independent variable was the infant's nutritional source (exclusive breastfeeding and breastfeeding supplemented with formula milk), while the dependent variables included weight gain and length gain. The data were analyzed univariately and bivariately. The normality test was performed using the Shapiro–Wilk test, and the difference analysis was performed using the independent t-test. The results showed that there was no significant difference in infant weight gain based on nutritional source (p = 0.334). However, there was a significant difference in infant length gain, with infants who were exclusively breastfed showing better linear growth than infants who received a combination of breast milk and formula (p = 0.006). The conclusion of this study shows that exclusive breastfeeding has a significant effect on infant length growth, but not on weight gain. These findings emphasize the importance of exclusive breastfeeding in supporting linear growth as a key indicator of healthy infant growth.